2019
DOI: 10.1111/tops.12455
|View full text |Cite
|
Sign up to set email alerts
|

The Scene Perception & Event Comprehension Theory (SPECT) Applied to Visual Narratives

Abstract: Understanding how people comprehend visual narratives (including picture stories, comics, and film) requires the combination of traditionally separate theories that span the initial sensory and perceptual processing of complex visual scenes, the perception of events over time, and comprehension of narratives. Existing piecemeal approaches fail to capture the interplay between these levels of processing. Here, we propose the Scene Perception & Event Comprehension Theory (SPECT), as applied to visual narratives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 178 publications
(272 reference statements)
8
90
0
1
Order By: Relevance
“…Facilitation was also found for targets with visually similar primes. These results are consistent with hypotheses generated from SPECT that the extent to which facilitation will be found depends upon the degree of spatiotemporal coherence between the contents of the current event model and new scene information (Loschky et al, 2019).…”
Section: Exploratory Analysis Of Conceptual Priming and Image Similaritysupporting
confidence: 89%
See 4 more Smart Citations
“…Facilitation was also found for targets with visually similar primes. These results are consistent with hypotheses generated from SPECT that the extent to which facilitation will be found depends upon the degree of spatiotemporal coherence between the contents of the current event model and new scene information (Loschky et al, 2019).…”
Section: Exploratory Analysis Of Conceptual Priming and Image Similaritysupporting
confidence: 89%
“…According to SPECT, one's understanding in the back end of what is happening in the current event (e.g., navigating through one's office toward the doorway) influences information extraction in the front end (Loschky et al, 2018;Loschky et al, 2019). In Experiment 1, we found that scenes presented in coherent sequences, which enabled observers to create a spatiotemporally coherent event model, were identified more accurately than scenes presented in randomized sequences.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations